CORRUPTION IMPACT ON EAST EUROPEAN EMERGING MARKETS DEVELOPMENT - Dobromirov, Dušan (The European Journal of Applied Economics, 2021)
This paper analyzes the impact of corruption level on East European financial markets development. Financial market liquidity for 15 national markets is presented and market volume per capita is used as an indicator for market maturity. Market volume per capita values are compared to corruption perception index values, using classical logic method. Findings of the research are quite interesting and unexpected, as they show modest impact of corruption on financial market development. Results raise some questions which are discussed in the paper.
Keywords: corruption; financial markets; market liquidity